Atomic entropy squeezing in three-level systems - Reboiro, Marta (2014)
We consider the problem of an atomic three-level system (in a ladder configuration) interacting with a radiation field. Assuming a coherent state as the initial state, we solve exactly the time evolution of the system. We discuss the appearance of atomic squeezing and calculate the atomic spin squeezing and the atomic entropy squeezing. We show that both parameters predict similar angular and time dependences.